2023
DOI: 10.21203/rs.3.rs-2994070/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fluvoxamine restores TFEB-mediated autophagy through Sigma-1R-controlled POM121 expression

Chun-Yu Lin,
Hsiang-En Wu,
Eddie Feng-Ju Weng
et al.

Abstract: Expansion of the GGGGCC-RNA repeat is a known cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), two conditions that currently have no cure. Recent studies have shown that activation of the Sigma-1 receptor plays an important role in providing neuroprotection, particularly in ALS and Alzheimer’s disease. However, the mechanisms underlying Sigma-1R activation and its effect on (G4C2)n-RNA-induced cell death remain unclear. In this study, we demonstrated that fluvoxamine is a Sigma-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The pathology of neurodegenerative disease compromises many biological processes, and thus it may be productive to investigate ancillary pathways, such as autophagy, to address issues in NPC homeostasis. To this end, several groups have studied the cytoplasmic mislocalization of the autophagic transcription factor, TFEB [ 94 , 116 , 344 , 345 ]. TFEB regulates the expression of lysosomal proteins, and studies in brain tissue from AD and ALS patients showed that this protein was mislocalized in disease [ 116 ], indicating convergence between defects in NCT and autophagy.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathology of neurodegenerative disease compromises many biological processes, and thus it may be productive to investigate ancillary pathways, such as autophagy, to address issues in NPC homeostasis. To this end, several groups have studied the cytoplasmic mislocalization of the autophagic transcription factor, TFEB [ 94 , 116 , 344 , 345 ]. TFEB regulates the expression of lysosomal proteins, and studies in brain tissue from AD and ALS patients showed that this protein was mislocalized in disease [ 116 ], indicating convergence between defects in NCT and autophagy.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Additionally, Sigmar1 overexpression restores Kapβ1-mediated nuclear import of TFEB, promoting autophagy [ 94 ]. Moreover, two Sigmar1 agonists, pridopidine and fluvoxamine, each promote POM121 expression and restore TFEB nuclear localization, and pridopidine protects against cell death [ 94 , 345 ]. Encouragingly, pridopidine has also been identified to have therapeutic potential in AD [ 347 ], PD [ 348 ], and HD [ 349 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%